The Role of Adipocyte Precursors in Development and Obesity - Ying, Tammy; Simmons, Rebecca A. (Frontiers in Endocrinology, 2021)
Maintenance of adipocyte precursors is critical for regulating metabolism and preventing obesity related disease. These precursors have been immortalized and studied in cellular models as well as – more recently – in animal models. However, little is known about adipocyte precursors from animals of different ages. Most research has focused on adipocyte precursors during obesity. This review goes over the most recent reports of adipocyte precursors during development and in adulthood. Some of these new analyses are due to new techniques such as single cell-RNA sequencing and temporally controlled lineage tracing. With these tools, we have been able to further our understanding of adipocyte precursor lineages and their different regulatory mechanisms. As we learn more about adipocyte precursor plasticity and regulation, we can hope to use this knowledge for future clinical applications.